Respuesta :
x= 12 + y
18x – 12y= 18
substitute x= 12 + y into 18x – 12y= 18
18x – 12y= 18
18(12 + y) – 12y= 18
36 + 18y - 12y = 18
6y =-18
y = -3
x= 12 + y
x= 12 -3
x = 9
solution (9, -3)
18x – 12y= 18
substitute x= 12 + y into 18x – 12y= 18
18x – 12y= 18
18(12 + y) – 12y= 18
36 + 18y - 12y = 18
6y =-18
y = -3
x= 12 + y
x= 12 -3
x = 9
solution (9, -3)
Since we have x=12+y simply use this value of x in the other equation to eliminate the x variable...
18(12+y)-12y=18 perform indicated multiplication on left side
216+18y-12y=18 combine like terms on left side
216+6y=18 subtract 216 from both sides
6y=-198 divide both sides by 6
y=-33, which makes x=12+y become:
x=12-33
x=-21
So the solution to this system of equations is the point (-21, -33)
18(12+y)-12y=18 perform indicated multiplication on left side
216+18y-12y=18 combine like terms on left side
216+6y=18 subtract 216 from both sides
6y=-198 divide both sides by 6
y=-33, which makes x=12+y become:
x=12-33
x=-21
So the solution to this system of equations is the point (-21, -33)